Governmental communication and socio-environmental conflict management - Macassi Lavander, Sandro (2012)
This article explores the State and its units of conflict management’s capacitiesand limitations to transform social environmental conflicts. The analysis  focuses on the type of intervention that Peruvian governments had been using in the media arena in response to the escalation of public conflicts. Furthermore, the article also focuses on how the government can use the information to play a role in the transformation and prevention of conflicts. Lastly, the discussion considers how the government handles its communication engagement and strategy with the citizens through conflict management -from a governance and public value perspective. The article concludes that the communication dimension is part of any government conflict management approach; therefore, it should be embedded within a national system for conflict management that puts the priority in the prevention and transformation of conflicts, rather than on the administration of crisis.